2019
DOI: 10.1186/s40816-019-0137-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-inflammatory activity of Justicia secunda Vahl leaf extract using in vitro and in vivo inflammation models

Abstract: Background: Justicia secunda Vahl. is a medicinal plant used in ethnomedical practice as therapy to manage inflammation. Therefore, this study was designed to evaluate the anti-inflammatory activity of methanol extract of J. secunda leaves (MEJSL) using in vitro and in vivo inflammation models. Methods: Seventy-percent MEJSL was prepared following standard procedure. In vitro anti-inflammatory assays were performed using heat-induced bovine serum albumin (BSA) denaturation and erythrocyte membrane stabilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 43 publications
4
13
0
Order By: Relevance
“…In the present work, rat paw edema induced by carrageenan is a widely used test for the determination of anti-inflammatory activity of pharmacological substances ( El-Serwy et al., 2013 ; Ammar et al., 2016 ). Intra-planter injection of carrageenan in rats resulted in an increase in rat's paw volume indicating edema in the non-treated group, which is consistent with previous studies ( Ammar et al., 2016 ; Anyasor et al., 2019 ; Santos et al., 2019 ). It has been shown that the injection of carrageenan into the sub-planter surface of rat paw promote a biphasic edema.…”
Section: Discussionsupporting
confidence: 91%
“…In the present work, rat paw edema induced by carrageenan is a widely used test for the determination of anti-inflammatory activity of pharmacological substances ( El-Serwy et al., 2013 ; Ammar et al., 2016 ). Intra-planter injection of carrageenan in rats resulted in an increase in rat's paw volume indicating edema in the non-treated group, which is consistent with previous studies ( Ammar et al., 2016 ; Anyasor et al., 2019 ; Santos et al., 2019 ). It has been shown that the injection of carrageenan into the sub-planter surface of rat paw promote a biphasic edema.…”
Section: Discussionsupporting
confidence: 91%
“…In the second part of this work, the antiinflammatory effect of the extract was assessed by the test of protein denaturation using BSA. The protein denaturation process is one of the multiple causes inducing an inflammatory response through the degeneration, the loss of tissue functionality, and the secretion of pro-inflammatory mediators [42]. The test is based on measurement of the capacity of the extract to prevent the loss of protein structure induced by the heat.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory markers are released by the lysis of lysosomal membranes during chronic inflammation which activates neutrophils, proteases and histamines at local site of tissue damage causing type III hypersensitivity reactions as well as the diseases like serum sickness. 20,21 As conventional NSAID, acetyl salicylic acid (aspirin) not only blocked COX enzyme and synthesis of endogenous PGE2 but also found to suppress the process of protein denaturation. 22 However, the leaf extract mimicked the NSAID to a moderate extent showing similar pattern in results.…”
Section: Discussionmentioning
confidence: 99%